Can dorzolamide/timolol-fixed combination effectively treat primary open-angle glaucoma?: A protocol for systematic review and meta-analysis. Issue 47 (20th November 2020) - Qi, Yan-Xiu; Liu, Hong-wei; Sun, Quan; Su, Xing-jie; Han, Lin
Abstract: Background: Primary open-angle glaucoma (POAG) is a very common disorder, and it is the second leading cause that results in blindness worldwide after cataracts. Previous studies have reported that dorzolamide/timolol-fixed combination (DTFC) can be used in treating POAG. However, there are still inconsistent results. Thus, this study will systematically investigate the efficacy and safety of DTFC on POAG. Methods: A comprehensive search will be carried out in Cochrane Library, MEDLINE, EMBASE, CINAHI, ACMD, China National Knowledge Infrastructure, and WANGFANG database from origin to the present. There are no limitations related to the language and publication status. Only randomized controlled trials that assessed the efficacy and safety of DTFC for the treatment of POAG will be included. Two researchers will independently undertake record selection, data extraction, and study quality assessment. Any divisions will be solved by discussion with a third researcher. We will perform statistical analysis using RevMan 5.3 software Results: This study will summarize the present evidence to identify the efficacy and safety of DTFC in treating POAG through mean intraocular pressure, best corrected visual acuity, contrast sensitivity, bioelectric activity of the retina, rate of progression of glaucoma, quality of life, and adverse events. Conclusions: The results of this study will provide evidence of DTFC for the treatment of POAG. Systematic review registration: INPLASY202040120.